2011
DOI: 10.1111/j.1467-9922.2010.00627.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Congruency and the Acquisition of L2 Morphemes

Abstract: The present study examined the proposal that the presence of a similar morpheme in the learner's first and second languages (L2) facilitates morphological development in the L2. Advanced Russian and Japanese speakers of English as a second language performed a self-paced reading task in which they read English sentences word by word for comprehension. Russian participants showed a reliable sensitivity to plural errors, but Japanese participants did not. The findings supported the morphological congruency hypot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
113
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(130 citation statements)
references
References 37 publications
9
113
4
Order By: Relevance
“…The current investigation thereby expands the range of nativelike agreement processing to include a context in which there is no grammar violation. The potentially limiting role of the L1 remains an open question that can only be resolved for certain by further research on subject-verb number agreement, but a self-paced reading study by Jiang, Novokshanova, Masuda, and Wang ( 2011 ) of the processing of plural morpheme errors (e.g., They discovered one of the dinosaurs/*dinosaur . Differences in either the participants' native languages (Chinese vs. English) or their profi ciency levels might account for the discrepancy between Jiang's results and those from the current experiment.…”
Section: Discussionmentioning
confidence: 99%
“…The current investigation thereby expands the range of nativelike agreement processing to include a context in which there is no grammar violation. The potentially limiting role of the L1 remains an open question that can only be resolved for certain by further research on subject-verb number agreement, but a self-paced reading study by Jiang, Novokshanova, Masuda, and Wang ( 2011 ) of the processing of plural morpheme errors (e.g., They discovered one of the dinosaurs/*dinosaur . Differences in either the participants' native languages (Chinese vs. English) or their profi ciency levels might account for the discrepancy between Jiang's results and those from the current experiment.…”
Section: Discussionmentioning
confidence: 99%
“…In other studies, however, late L2 learners were asked to process some syntactic features that had no equivalent in their native languages, and these studies reported non-native-like behaviours from late L2 learners (Chen et al, 2007;Ojima, Nakata, & Kakigi, 2005). Jiang (2011) raised the Morphological Congruency Hypothesis to examine the effect the crosslinguistic difference of a particular morpheme might have on late bilinguals' on-line processing of L2. They claimed that two languages are morphologically congruent when both grammaticalize and mark a meaning morphologically.…”
Section: Introductionmentioning
confidence: 98%
“…They hypothesized that only congruent grammatical morphemes (i.e., those morphemes that exist in both the L1 and the L2) can be automatically processed by high-proficiency L2 learners; incongruent morphemes are difficult to be on-line processed. Jiang (2007Jiang ( , 2011) used a self-paced reading paradigm to examine bilinguals' sensitivity to the violation of nouns' plurality and verb subcategorization in English. Their participants were late bilinguals (came to US in their 20s or at an older age), and were from different L1 backgrounds: Chinese (2007) and Russian and Japanese (2011).…”
Section: Introductionmentioning
confidence: 99%
“…Overtness of functional morphology plays a role in predictions about learner behavior, such, for example, that L2 overt morphology is easier to acquire when your native language has a similar affix. For instance, Jiang, Novokshanova, Masuda, and Wang (2011) showed that Russian learners of English, unlike Japanese learners, were reliably sensitive to English plural errors in an online task. The authors attributed this differential sensitivity to Russian having overt plural morphology while Japanese lacks such morphemes.…”
Section: Toward the Here And Nowmentioning
confidence: 99%